Pentingnya Penggunaan Media Realia Untuk Meningkatkan Hasil Belajar Peserta Didik - Riyanti, Fitria (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In essence, the teaching and learning process cannot be separated from the role of the media. There are various learning media, each of which has its own strengths and weaknesses. Therefore, as an educator, you must be wise in choosing appropriate learning media for the material to be taught. One of the learning media that must exist in learning is realia media. Media Realia is a learning resource in which it contains messages that involve the sense of sight or subject matter that is made interesting in a real (imitation) form. So that it makes students not bored in participating in learning, and student learning outcomes also increase. Realia media has advantages, namely: Easy to find, because realia media is a real media that is around the environment. Provide clear and accurate information. It doesn't take much time to prepare. While the weaknesses are: The size of the realia media is too small or too large so it requires another object or room to see it. The risk of bringing students to see real media outside the school environment. It costs a lot of money to hold real media objects.